Investigation of factors that induce premarital sexual intercourse among adolescents in secondary schools in Nigeria (2019)
Adolescence is a period of life that is characterized by dramatic changes in biological processes in physical and social contexts. The period can be demanding and challenging because adolescents are pre-occupied with self- identity, self-image and acceptability in the society as well as self- awareness since the action to be taken is a big part of person’s life in the future particularly on whether or not to engage in premarital sexual intercourse. This study investigated factors that induce adolescents to engage in premarital sexual intercourse among secondary school students in Nigeria. The study was guided by three research questions and one hypothesis and adopted survey research design. Multistage sampling technique was used to sample 600 students from all the six geo-political zones in Nigeria. One instrument with reliability coefficient of 0.79 was used for data collection. Descriptive and Inferential statistics was used to analyze the data collected, Finding shows that previous sexual abuse experience (75%) was the most potent factor that induces premarital sexual intercourse and four of the of the independent variables showed significant contribution to the dependent variable: previous sexual abuse experience ((3 = .290, p<.05), smoking of prohibited drugs ({3 = -.345, p<.05), peer influence (p = .225, p<.05), poor housing condition (p = .126, p<,05). It was recommended that adolescents should avoid engaging in premarital sexual intercourse and reduce curiosity about sex.